DIMENSI NILAI DALAM ACARA KUMPUL KOPE - Vinsensius Sumardi; Aleksius Jeka; Vitalis Tarsan (Jurnal Literasi Pendidikan Dasar (JLPD), 2022)
The people of Manggarai as part of one of the community groups certainly have habits. These habits can become the uniqueness and wealth of the Manggarai people. The customary practices carried out by the Manggarai community certainly contain positive meaning and benefit for the common good of the Manggarai community. One of the habits that is often done by most people is kumpul kope. The practice of kumpul kope displayed by the Manggarai community certainly contains positive meaning and benefits for the common good of the Manggarai community. This study aims to explore and find positive values ​​hidden behind the habit of kumpul kope carried out by the community in Lalong village, South Lembor sub-district, West Manggarai Regency. This research design uses a qualitative approach with observation and interview techniques. Data from observations and interviews were then processed with the stages of reduction, presentation, and drawing conclusions. The results showed that kumpul kope is a habit by the people of Lalong village, South Lembor District, West Manggarai. In general, kumpul kope aims to raise money in order to help the prospective groom in financing the marriage process. More than that, the kumpul kope rite actually puts forward the application of togetherness, economic, solidarity and social values ​​for the community.